O gato comeu a sua língua? A metáfora conceptual nos instrumentos de avaliação padronizados e no processo de reabilitação da habilidade de leitura em casos de afasia - Silva, Larissa Rizzon da (My University, 2021)
Aphasia is a language disorder, caused by an acquired brain lesion, which compromises linguistic performance - oral and/or comprehension. The assessment and rehabilitation process of reading skills in cases of aphasia have never been easy tasks developed in the clinical context, as the methodology chosen by the professional is not always the most relevant. Thus, this research aims to propose improvements to standardized assessment instruments and the process of rehabilitation of reading skills in cases of aphasia, based on the theory of conceptual metaphor. With regard to the method, it is a qualitative research at an exploratory level. First, it investigates the conception of reading, through studies by Kleimann (2004, 2013), Halliday (1989), Kilian and Flôres (2012), among others; and conceptual metaphor, based on the literature developed by Lakoff and Johnson (1980, 2002), Kövecses (2005) and Evans and Green (2006). Then, the studies developed in Brazil in the last twenty years on the subject in question are analyzed, in order to verify if in this process conditions are made available for the aphasic to understand and interpret the conceptual metaphors present in a text. Subsequently, the main standardized assessment instruments used in the Brazilian speech therapy clinic in cases of aphasia are analyzed, namely: the Token Test (1962), the Boston Diagnostic Aphasia Examination (BDAE) (1983); the M1-Alpha Test (1993); the Montreal Communication Assessment Battery - short version (MAC B Battery); and the Montreal-Tolouse Language Assessment Battery (MTL) (2016). Finally, improvements are proposed for each of the aforementioned batteries. Through this research, it is concluded that, considering that metaphor is conceptual, conventional and pervasive to language, it is believed that all activities aimed at investigating reading ability should include the analysis of understanding and metaphorical interpretation, since that reading success depends not only on word identification, fluency, lexical knowledge and context, but also on the interpretation of inferences and metaphors. [resumo fornecido pelo autor]
A afasia consiste em um distúrbio de linguagem, causado por uma lesão cerebral adquirida, que compromete o desempenho linguístico - expressivo e/ou compreensivo. A avaliação e o processo de reabilitação da habilidade de leitura em casos de afasia nunca foram tarefas fáceis desenvolvidas no âmbito clínico, pois a metodologia escolhida pelo profissional nem sempre é a mais pertinente. Desta forma, esta pesquisa objetiva propor melhorias aos instrumentos de avaliação padronizados e ao processo de reabilitação da habilidade de leitura em casos de afasia, a partir da teoria da metáfora conceptual. No que tange ao método, trata-se de uma pesquisa de natureza qualitativa de nível exploratório. Primeiramente, investiga-se a concepção de leitura, através dos estudos de Kleimann (2004, 2013), Halliday (1989) Kilian e Flôres (2012), entre outros; e de metáfora conceptual, com base na literatura desenvolvida por Lakoff e Johnson (1980, 2002), Kövecses (2005) e Evans e Green (2006). Em seguida, analisam-se os estudos desenvolvidos no Brasil nos últimos vinte anos sobre o tema em questão, a fim de verificar se nesse processo são disponibilizadas condições para que o afásico compreenda e interprete as metáforas conceptuais presentes em um texto. Posteriormente, são analisados os principais testes-padrão utilizados na clínica fonoaudiológica brasileira em casos de afasia, sendo eles: o Token Test (1962), o Boston Diagnostic Aphasia Examination (BDAE) (1983); o Teste M1-Alpha (1993); a Bateria Montreal de Avaliação da Comunicação Breve (Bateria MAC B) (2008/2014); e a Bateria Montreal-Tolouse de Avaliação da Linguagem (MTL) (2016). Por fim, são propostas melhorias em cada uma das baterias supracitadas. Através desta pesquisa, conclui-se que, ao considerar que a metáfora é conceptual, convencional e pervasiva à linguagem, acredita-se que a maioria das atividades que se propõem a investigar a habilidade de leitura poderia contemplar a análise da compreensão e da interpretação metafórica, visto que o sucesso da leitura depende não só da identificação de palavras, da fluência, do conhecimento lexical e do contexto, como também da interpretação de inferências e metáforas. [resumo fornecido pelo autor]
Keywords: Afasia; Leitura; Linguística; Neurolinguística; Comunicação escrita; Aphasia; Reading; Linguistics; Neurolinguistics; Written communication